A New Theory and Its Applications: Fluids in Mesopores - Harald Morgner (Challenges and Advances in Chemical Science Vol. 1, 2021)
Although hysteresis in fluid adsorption in porous material has been known for over a century, the thermodynamic treatment of this phenomenon is still unspecified. We suggest recognising that thermodynamics is not designed to deal with constrained systems and creating a new set of rules to explain their behaviour. The basis for this suggestion is a significant number of simulation calculations. The simulation method used has been shown to describe both static and dynamic processes in this field [1]. The newly proposed theory takes into account the occurrence of hysteresis without inconsistencies Further, it will be shown, that the theory allows simulating diffusional and convectional transport (nanofluidics) by a unified ansatz without the need to introduce capillary forces (surface or interface tensions) by phenomenological parameters. The possibility for practical use is discussed in the second section of the study. It turns out that the new ideas pave the way for better applications by allowing for the use of unique states of matter observed in porous systems. We’ll concentrate on the possibilities of driving a fluid in a pore into negative-pressure states under static and dynamic settings. It turns out that states with negative pressure can be reproducibly controlled. Negative pressure states have been understood in principle since Torricelli’s time, and they have been explored as experimentally accessible conditions in the literature. Despite this, they have not been translated into functional utility, which is most likely due to the concept of their metastability in macroscopic systems. The topic of metastability has been discussed widely in the literature. Possible applications refer to controlling chemical reactions as well as new routes to efficient separation processes that are difficult to handle by conventional techniques.